Evaluation of peripheral blood mononuclear cell collection by leukapheresis. Issue 5 (12th February 2019) - Chen, Jian; Goss, Cheryl; Avecilla, Scott T.; Hong, Hong; Walsh, Eileen; Wuest, David; Maslak, Peter; Pessin, Melissa S.
Abstract : BACKGROUND: Adoptive immunotherapy using engineered lymphocytes has shown promising results in treating cancers even in patients who have failed other treatments. As the first essential step, the number of peripheral mononuclear cell (MNC) collection procedures is rapidly increasing. In this retrospective study, we reviewed the collection results to determine factors that affect MNC collection. STUDY DESIGN AND METHODS: We reviewed 184 collections that were performed on 169 adult allogenic donors and patients with acute lymphoid leukemia, chronic lymphoid leukemia, lymphoma, multiple myeloma, or solid‐organ tumors. All the leukapheresis procedures were performed after a complete cell count with differential was obtained. Total blood volume (TBV) was defined as processed blood volume divided by patient blood volume. RESULTS: There was a significant association between the precollection MNC count (pre‐MNC) and the MNC yields normalized by TBV (r = 0.926; p < 0.001) and a regression formula was created to predict MNC yields. Multiple regression analyses showed that pre‐MNC, TBV, and precollection hemoglobin were strongly associated with MNC yield (R 2 = 0.866; F (3180) = 388.472; p < 0.001), and pre‐MNC had the greatest influence on MNC yield (β = 0.960; p < 0.001) followed by TBV (β = 0.302; p < 0.001), and Hgb (β = 0.136; p < 0.001). CONCLUSION: Our results suggest that the optimal time for MNC collection can be determined based on pre‐MNC and that processing volume should be determined based on collection goal and pre‐MNC to optimize and personalize the harvesting procedure.